Water Bears (Tardigrada) of the Bieszczady Mountains (Poland, West Carpathians) - Michalczyk, Łukasz; Kaczmarek, Łukasz (Zootaxa, 2003)
Twenty-seven species of Tardigrada were found in 278 samples collected from the Bieszczady Mountains in April and May of 2001. Twelve were recorded for the first time from this region: Astatumen bartosi (W“glarska, 1959); Calohypsibius schusteri Nelson & McGlothlin, 1996; Diphascon (Adropion) prosirostre Thulin, 1928; Echiniscus merokensis Richters, 1904; Echiniscus trisetosus Cuénot, 1932; Isohypsibius pappi (Iharos, 1966); Isohypsibius ronsisvallei (Binda & Pilato, 1969); Isohypsibius sattleri (Richters, 1902); Isohypsibius schaudinni (Richters, 1909); Macrobiotus crenulatus Richters, 1904; Macrobiotus macrocalix Bertolani & Rebecchi, 1993 and Murrayon hibernicus (Murray, 1907). C. schusteri and M. crenulatus were new to the fauna of Poland, and C. schusteri and I. ronsisvallei were also new to the Carpathian fauna. Three other species Echiniscus reticulatus Murray, 1905, Hypsibius dujardini (Doyere, 1840) and Pseudechiniscus suillus (Ehrenberg, 1853) previously recorded from the Bieszczady Mts. were not confirmed in this study. A key to determine the known species from the Bieszczady Mts. is given. Taxonomical and zoogeographical remarks on these species are also given.